Circulating micro RNA in insulin resistant horses - da Costa Santos, Hugo F., author; Hess, Tanja, advisor; Landolt, Gabriele, committee member; Bruemmer, Jason, committee member; Coleman, Stephen, committee member; Engle, Terry, committee member (Colorado State University. Libraries, 2018)
Insulin resistance is a prevalent pathophysiological disorder among domestic horses and is associated with many other conditions such as abnormal adiposity, chronic low-grade systemic inflammation, equine metabolic syndrome, and pituitary pars intermedia dysfunction. However, the processes leading to equine insulin resistance and associated conditions remain a subject of study. Studies in human and laboratory animals have shown that a class of small non-coding RNAs, known as microRNAs (miRNAs), are involved in the regulation of many biological processes and are associated with many diseases. MiRNAs have emerged as potential biomarkers in studies for the diagnosis and prognosis of many diseases, including type 2 diabetes and metabolic syndrome. Profiling circulating miRNAs allows researchers to understand further the mechanisms involved in many diseases, including type 2 diabetes mellitus and metabolic syndrome in humans, and it has excellent potential for equine medicine. In our pilot study, we hypothesized that insulin resistant horses would have a different circulating miRNA profile than those that are healthy. 6 mares were selected from an initial population to represent the most insulin-sensitive (n = 3) and insulin resistant (n = 3) states. Serum samples were collected for miRNA profiling of these animals, investigating the presence and relative amount of 340 equine miRNAs. Results showed different miRNA profiles between groups, with a total of 14 miRNAs differently expressed between insulin resistant and insulin sensitive animals. Furthermore, results of this preliminary study suggested circulating miRNA profiles as potential new tools for evaluating the mechanisms of insulin resistance in horses and the development of novel diagnosis and treatment methods for this condition in equines. The current study aimed to follow up the pilot study by increasing the number of animals undergoing miRNA profiling and including both horses and ponies for testing. It was hypothesized that insulin resistant animals (horses and ponies) would have a different circulating miRNA profile than those that are healthy. Additionally, circulating miRNA profiles of horses and ponies were also compared. Two initial populations, one of horses and one of ponies, were screened for their insulin sensitivity state using basal proxies for insulin and glucose. Selected animals, 12 non-pregnant Thoroughbred/ Thoroughbred-cross and 12 non-pregnant Welsh/Dartmoor mares were evaluated for insulin sensitivity with the frequent sampling intravenous glucose tolerance test (FSIGTT), and serum samples collected for miRNA profiling. The quantification of miRNAs was done through qRT-PCR analysis performed to investigate the presence and relative amount of 340 equine miRNAs. Confirmation by quantitative real-time polymerase chain reaction revealed that miRNA was present in the serum of all animals. After diagnosis based on the FSIGTT results, mares were divided into groups representing their insulin sensitivity state: insulin sensitive (IS, n = 13, ten horses and three ponies) or insulin resistant (IR, n = 11, two horses and nine ponies) animals, and their miRNA profile compared. Results demonstrated that from the 340 miRNAs analyzed, 13 miRNAs were differentially expressed between insulin resistant and insulin sensitive horses, 15 differently expressed between insulin resistant and insulin sensitive ponies, 17 differently expressed between horses and ponies, and 14 differently expressed between insulin resistant and insulin sensitive animals, horses and ponies combined (p<0.05), with 4 of these miRNAs already noted when comparing horses versus ponies. In the horse groups, three miRNAs were expressed in the insulin resistant group only. Finally, eight circulating miRNAs are proposed as potential regulators of equine insulin resistance. The results of this study, in addition to our preliminary investigation, suggest potential new tools that could be used to understand further the mechanisms involved in equine insulin resistance and associated conditions and for the development of new, practical and efficient diagnosis and prognosis methods for this condition in horses.